How Apocalyptic Disrupts Theological Tradition - Hinlicky, Paul R. (Pro ecclesia, 2024)
Coming from a theologian who has maintained a high medieval view of Nicene Orthodoxy against the ravages of Augustinianism, this review essay of David Bentley Hart's Tradition and Apocalypse excavates the unspoken liberal Protestant provenance of his historicist critique of predominant notions of sacred tradition in Orthodox and Catholic circles. Critiques of John Henry Newman and Maurice Blondel demonstrate this claim. His appeal to apocalyptic is also shown silently to rely upon the twentieth-century rediscovery of biblical apocalyptic, from yet another quarter of Protestantism. The apocalyptic ferment of the gospel issuing in doctrinal novelty is illustrated by the Nicene theology: Arius is the defender of traditional formulas and Athanasius the innovator. Yet at the decisive juncture, Hart retreats from the prosecution of bad faith dogmatism, shoring up failed Christendom to find consolation in the metaphysics of the Good. This move, however, leaves him on the horns of a dilemma.